Effectiveness of Educational Statistics Learning Modules - Abdul Wahab; Akhmad Syahid; Junaedi Junaedi (Universitas Negeri Makassar, 2023)
This research was carried out at the Faculty of Islamic Religion, Indonesian Muslim University, Educational Study Program, with the aim of this research being to determine the effectiveness of the Educational Statistics learning module. The research method uses a quantitative research type with an experimental One Group Pretest-Postest Design approach, with a sample of 20 students from the education study program at the Faculty of Islamic Religion, Indonesian Muslim University (FAI-UMI). The results of the research show that the results of the analysis, fulfilling the assumptions of normality and homogeneity, as well as hypothesis testing using the paired t test, show that the average value of post-test Educational Statistics learning outcomes is significantly different and much higher than the average pre-test Educational Statistics learning outcomes. So, it is concluded that the application of the Educational Statistics learning module is effective.